Random sampling over lca groups and inversion of the radon transform - Porten, Erika (2021)
We consider the problem of reconstructing a measurable function over G from a countable subset ofsamples, taken accordingly to a Poisson random point process, when G is a locally compact abelian group. Thisresults are applied to the problem of approximating the inverse Radon Transform of a function.